Health shocks and child time allocation decisions by households: Evidence from Ethiopia - Yonatan Dinku; David Fielding; Murat Genç (IZA Journal of Labor Economics, 2018)
Little is currently known about the effects of shocks to parental health on the allocation of children's time between alternative activities. Using longitudinal data from the Ethiopian Young Lives surveys of 2006 and 2009, we analyse the effect of health shocks on the amount of children's time spent in work, leisure and education. One key contribution of the paper is that we distinguish between child labour as defined by organisations such as the International Labour Organisation and other types of child work, such as light domestic chores. We find that paternal illness increases the time spent in income-generating work but maternal illness increases the time spent in domestic work. Moreover, maternal illness has a relatively large effect on daughters while paternal illness has a relatively large effect on sons. Overall, parental illness leads to large and significant increases in the amount of child labour.
Keywords: D13; I12; I21; O15; 330; Parental illness; Child labour; Ethiopia